An Evaluation of the Innovative Services of Public Libraries Applying Project Activities - Stasėnaitė, Violeta; Orlakaitė, Gabija (Information & Media, 2018)
A global, dynamic and creative environment of the information society designs new users’ information needs, and it incites information and memory institutions to look for innovative forms and ways to meet these needs and create new services. Project activities are a new area of library activities, providing an opportunity to expand the package of services. The evaluation of the outcome of the project activities – new services – is one of the most important ways to show that a library is useful and valuable for certain groups in society. This article deals with the links between innovativeness and the project activities of libraries, raising a question for empirical research: how does the society participating in project activities of libraries evaluate the innovative services developed during the projects? The conducted research presents the quality of services developed by the Šiauliai District Municipality Public Library during the projects carried out in 2015–2016 from the users’ viewpoint in accordance with the evaluation criteria defined in the SERVQUAL service quality measurement methodology, i.e., reliability, assurance, tangibles, empathy and responsiveness. The research shows that undertaking project activities is necessary for the modern public library, as it increases the attractiveness of the library, improves its image and attracts new users. The willingness of users to participate in future projects reveals that such criteria of activities as responsiveness, assurance and empathy are evaluated positively. The respondents positively evaluate the benefit provided by project activities. They mostly emphasize the opportunity to broaden their intellectual horizons, purposefully spend leisure time and become more active and sociable.